Continuous Deoxygenation of Triglycerides to Biofuels Over 15Co5Ni/g-Al2O3 Catalyst - Huang, Xi-Gen; Le, Zhi-Ping (Asian Journal of Chemistry, 2015)
Bio fuels production was carried out in an electrically heated fixed bed tubular reactor. During the experimental work, all kinds of factor were investigated. It was found that reaction temperature played key role and the rate between nickel and cobalt is an important role in decarboxylation and decarbonylation reaction. Technological conditions are optimized at reaction temperature, the oil flow rate, the gas flow rate and the rate between nickel and cobalt, 450 °C, 0.1 mL/min, 12 mL/min and 3:1, respectively. The alkanes content and alkenes content of liquid products is 44.86 and 49.08 %, respectively under the optimized condition. The product is mostly under C18 hydrocarbon compounds. The results of GC online and trace water determination show that the oxygen in the oils are mainly removed through decarboxylation and decarbonylation reaction. The oxygen in the oils are tiny removed through the dehydration of alcohol. Characterization of technologies including TG, XRD, BET, FT-IR, GC-MS and temperature programmed reduction were performed to demonstrate more details. The catalyst deactivation was due to coke deposition, relatively to sintering.